Investigating the Epidemiology and Socioecological Dynamics of Hydatid-like Cysts Within a Specific Endemic District - Muhammad Irfan Khan; Rahmat Ali; Dejun Ji; Wei Lan; Ahmed A. Saleh; Shahab Ur Rehman; Muhammad Shuaib; Shah Zeb Ahmad; Hussain; Xi Wu (Animals)
Cystic Echinococcosis (CE) is a significant zoonotic parasitic disease caused by Echinococcus cestode parasites, affecting a variety of animals, including humans and wildlife, with serious implications for public health. In Pakistan, CE continues to pose a considerable public health challenge, impacting the livestock sector and wildlife conservation due to its economic and socio-cultural ramifications. This study aimed to examine the frequency of lesions indicative of Echinococcus cysts in livestock across several slaughterhouses in Khyber Pakhtunkhwa (KP), with the data collection occurring from May 2022 to February 2024. A total of 1120 animals, including 455 buffaloes, 295 cows, 200 sheep, and 170 goats, were assessed. The overall CE prevalence was found to be 5.7% (95% CI: 4.3–7.0%; 63 out of 1120), with the highest frequency in buffaloes (6.6%; 95% CI: 4.3–8.9%) and the lowest in goats (2.9%; 95% CI: 0.4–5.5%). Female animals demonstrated a higher infection rate (6.3%; 95% CI: 4.4–8.1%) compared to males (4.7%; 95% CI: 2.8–6.7%), with the liver being the most frequently affected organ (55.0%; 95% CI: 41.7–66.3%). Additionally, a survey of 200 respondents revealed that 74.5% of farmers were unaware of CE, and only 14.5% were taking preventive measures against parasites. These findings suggest a potential decline in the prevalence of this parasitic disease, likely due to advancements in veterinary services and modern farming practices.